A multi-analytical approach for the study of Neolithic pottery from the great Dolmen of Zambujeiro (Évora, Portugal) - MANHITA, A. (2014)
The Great Dolmen of Zambujeiro (GDZ), built between the )th and the middle of the Crd millennium BC, between the late Neolithic and Chalcolithic periods, is located on the right margin of Peramanca riverside, in Valverde, municipality of Évora (Portugal), and is one of the largest megalithic monuments on the Iberian Peninsula. The GDZ was identified and excavated between (lm) and (lmp by Henrique Leonor Pina and is classified as a national monument since (lo). During the p's decade of last century, due to the monument degradation, some conservation works were carried over under the direction of Caetano Mello Beirão, and some archaeological research was also performed.